ANALISIS SOAL SEJARAH KEBUDAYAAN ISLAM MI ‎KELAS IV PERSPEKTIF HOTS - Cahayaningsih, Ica Putri (Ta'allum: Jurnal Pendidikan Islam, 2020)
Analysis of the items is adjusted to the material provided in the textbook, whether the questions available in the book or not, because in some cases it not in accordance with the questions. in addition the authors, also analyzed the items contained in the book with HOTS qualification categories based on Bloom’s Taxonomy. this study aims to describe wether the questions presented in thr studebt book (BSE) History of Islamic culture class IV curriculum 2013 published by Ministry of Religion in 2014 aew in accordance with the level HOTS category in Bloom’s Taxonomy. The data analyzed in this study are the study questions presented in the student’s book. The analysis technique used in the research is descriptive statistical analysis and with resulting data in the form of percentages. The result of the analysis in this study indicate that the questions contained in the SKI student book are presented with the proportion (1) 78% of questions in LOTS category, (2) 21% of questions in the MOTS category, and (3)1% of questions in the HOTS category. Thus, it can be concluded that the questions prsentes in the SKI student book are not ideal as matter of practice.